2018
DOI: 10.3201/eid2408.180063
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Influenza B Virus Epidemiology by Lineage, China

Abstract: We used national sentinel surveillance data in China for 2005–2016 to examine the lineage-specific epidemiology of influenza B. Influenza B viruses circulated every year with relatively lower activity than influenza A. B/Yamagata was more frequently detected in adults than in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 14 publications
5
38
0
1
Order By: Relevance
“…It should be noted that another peak of RR in high temperature for Flu-A was observed in the study. This finding was supported by previous studies, which reported the semiannual epidemic in the summer in subtropical cities in China (Yang et al, 2018a;Yang et al, 2018b;Ye et al, 2019). The potential reasons for this semiannual epidemic required further research.…”
Section: Discussionsupporting
confidence: 87%
“…It should be noted that another peak of RR in high temperature for Flu-A was observed in the study. This finding was supported by previous studies, which reported the semiannual epidemic in the summer in subtropical cities in China (Yang et al, 2018a;Yang et al, 2018b;Ye et al, 2019). The potential reasons for this semiannual epidemic required further research.…”
Section: Discussionsupporting
confidence: 87%
“…A relatively high B/Yamagata percentage was found in older adults in the present study. These results are consistent with the results of recent studies in China, and which may be explained by exposure to the virus early in life and genetic difference [13,14,21]. In China, influenza vaccination is mostly self-paid, with all-age coverage as low as 2% [5].…”
Section: Discussionsupporting
confidence: 91%
“…The positive rate was calculated by dividing the number of samples positive for influenza virus by the total number of samples tested. The age-specific influenza positive rate by subtype/lineage was calculated as the number of sentinel specimens testing positive for each subtype/lineage (numerator) among the ILI cases recruited for specimen collection (denominator) in each corresponding age group [21].…”
Section: Discussionmentioning
confidence: 99%
“…Influenza A virus infection has gained much more attention because of its high morbidity and mortality. Influenza B virus infection is found to be as serious as influenza A virus infection in terms of substantial hospital admissions and deaths worldwide every year (Dawood et al, 2010;Paddock et al, 2012;Yang et al, 2018). An epidemic of influenza B occurred in China during winter 2017-2018.…”
Section: Introductionmentioning
confidence: 99%